Pemberdayaan Pelaku Usaha UMKM Sambel Pecel Bapak Affandi Melalui Digital Marketing E-Commerse Shopee - Mina, Rosyida El; Pangestu, Melvya Maharani; Samudra, Rosanda Dewi; Handayani, Salsa Billa; Susilo, Eko Adi (Kontibusi: Jurnal Kontribusi Kepada Masyarakat, 2023)
Empowerment of MSMEs is a business that always one of its business groups can be used as a determinant or mainstay in managing the business city planning of an area based on a people's economy. Technology has developed in the marketing field, namely digital marketing. Where digital marketing has an important role in promoting a product that can target consumers efficiently and relevantly. The MSMEs targeted are MSME Sambal Pecel Hanifah owned by Mr. Ahmad Affandi which is located in Ngaglik Village, Srengat District, Blitar Regency. By using the market place is expected to reach a wider range of consumers. In the analysis of the implementation method, the way of marketing promotion of a product is not optimal because product sales are not stable or depend on product orders. Therefore, from these problems, digital marketing training was held to introduce how to create a store in the Shopee market place and its use. The results of the digital marketing training were carried out well according to plan and MSME owners understand and master digital marketing in the Shopee market place.